Succeeding a Family Business in University: The Role of Family Business Exposure on Students' Entrepreneurial Intention - Bongiarto, Jeanny Lorenza; Permatasari, Anggraeni (International Journal of Family Business Practices, 2025)
This study examines the entrepreneurial intention of students to continue their family business. Family business exposure is significant, but is not currently rooted in positivity. The paper aims to determine factors affecting students' intention to run or continue a family business. The factors examined four independent variables: entrepreneurial education, family business exposure, attitude, subjective norms, and self-efficacy. The study uses a quantitative research design and survey questionnaires as a methodology. The sampling technique used is purposive sampling, with a sample of 300 respondents. Partial least squares (PLS) is used to analyze the data. The results showed that entrepreneurship education and family business exposure positively and significantly influence attitude and self-efficacy in students' intention to start a business. Attitude and self-efficacy also influence entrepreneurial intention significantly. This study proved that entrepreneurship education does not influence subjective norms; subjective norms also do not significantly influence student intention to start a business. Meanwhile, the family business exposure has a positive and significant influence on subjective norms. This research explains factors affecting President University students' intention to start a business.